Specific Needs of Families of Deaf Parents and Hearing Children - Klimentová, Eva; Dočekal, Vít (Central European Journal of Educational Research, 2020)
The aim of the paper is to describe specific aspects of deaf parenting of hearing children, based on an interpretation of research findings concerning the target group. Deaf parents, isolated from the verbally communicating majority by their sensory disability, face the challenge of raising and preparing hearing children for life. Our research based on semi-structured interviews with both deaf parents and hearing children demonstrates, however, that these parents do not primarily describe their parenthood as difficult or complicated. They are reconciled to their handicap and its consequences and use tools in the social environment to overcome the disadvantages of deaf parenting. Some “children” (all our respondents were adults reflecting on their childhood) describe, in contrast, their experience as a gradual reverse of natural family roles, with children eventually navigating their parents around the hearing world. These results indicate the need for further activities with these target groups in social work.